Integrasi SWOT dan AHP dalam Pengelolaan Ekosistem Mangrove di Kawasan Wisata Bahari Gugusan Pulau Pari - Ferry Dwi Cahyadi; Nurul Khakhim; Djati Mardiatno (Jurnal Pariwisata Pesona, 2018)
Coastal ecosystems on small islands have a higher vulnerability than large islands due to limited resources and carrying capacity. Mangroves as one of the main ecosystems on the coast of small islands and close to human activities make this ecosystem more vulnerable to disturbance. This study aims to determine the factors that influence the management of mangrove ecosystems and combine SWOT and AHP methods in the strategic management of mangrove ecosystem in the Pari Islands. Data collection was carried out with literature reviews, in-depth interviews and focus group discussions. The results of the data collected are then analyzed into a combination of AHP method with SWOT or known as A'WOT. A'WOT is used to formulate mangrove ecosystem management strategies. The results showed that the strategy for managing mangrove ecosystems in Pari Islands was prioritized in opening up areas or activities for ecotourism.